Projovem Urbano: concepções de formação de jovens e implicações como política colaborativa (2005-2013) - Mascarenhas, Vanessa Batista (2016)
This research aimed to discuss the concepts of training young ProJovem Urban and their possible implications as Collaborative Policy from 2005 to 2013. The study was guided by the following question: What youth education conceptions ProJovem Urban and to what extent the views set out constitute expressions and as vectors of "Collaborative Policy" that has been guiding the Brazilian educational policies within the framework of the Skills education? This is on the assumption that public policies as a product of tensions, gives us in his studies reflect on the role of the state and society of competing projects. As a general objective sought to analyze the youth education conceptions of this program and its possible implications as Collaborative Policy. It was assumed as epistemological orientation a historical-critical perspective, in dialogue with authors such as Neves (2005), Ramos (2006) and Shiroma, Garcia and Campos (2011). In this context, the work has the categories of Youth analysis, Collaborative Policy and Education Skills. For the implementation of this research was used qualitative methodology and how the documentary research technique through content analysis method. The study was to sources, print and digital official documents that governed the ProJovem in the period 2005-2013, such laws, reports, projects, manuals and program advertising pieces, taking into account the context in which they were produced. The research showed that the ProJovem Urban presented as official discourse the prospect of full training, with emphasis on education of participatory citizen and entered the world of work, from the development of youth leadership. The study of the program revealed, however, that the concept of implicit training the proposal is based on the perspective of adaptation of young people to capitalist lines, by adapting to the demands of the labor market, aimed at the development of skills and values ​​development cooperation consistent with the Collaborative Policy. Thus, this program is in line with the formation of a collaborator man who seeks to exercise a new quality citizenship, but without questioning the essence of capitalism and social inequality whose results from it, the ProJovem Urban in its proposal for comprehensive training has implications as Collaborative Policy. Thus, the purpose of overcoming program the exclusion of young people is not made, the first not to be that the real intent of the program and secondly because the IBGE data indicate that young people, the program's target audience, remain in precarious social conditions with low income and inability to balance work and study.